Work Life Balance, Peningkatan Karir dan Tekanan Kerja terhadap Produktivitas: Kasus pada Lembaga Sertifikasi Profesi P3 Pembangun Penyuluh Integritas Bangsa - Dewi Puspaningtyas Faeni; Ratih Puspitaningtyas; Ravindra Safitra (Penerbit Goodwood, 2021)
Purpose: This study examined variables aimed at examining work-life balance, Career Improvement and work pressure towards productivity. Research methodology: This study was conducted on employees of LSP P3 PIB, examining of what is the correlation between the correlations of the three exogenous variable factors towards productivity as an endogenous variable. Sampling in this research was calculated using the Slovin formula using the Simple Random Sampling. The Respondents are 105 people, rounded up to 100 people. The respondents were employees of LSP P3 PIB. The methodological technique used for data collection is by distributing questionnaires from the firsthand source or Primary Data. The statistical test tool used is SmartPLS 3. Results: The conclusion of this study demographically, the majority of the respondent are women. The outcome of this research is that work-life balance (0.351) positively and significantly affects productivity, while Career (0.309) has a significantly positive effect, and stress (0.294) has a significant positive effect on productivity. Limitations: The limitation is that it is only conducted on variables that are studied and excluding other external variables with a limited number of respondents in less than one year. Contribution: The organization be more aware of the employees’ working engagement by supporting the employees to adjust their work schedule that is Work-Life Balance for their productivity.